2003
DOI: 10.1021/jp035680h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gold/Polypyrrole Core−Shell Nanocomposites and Elemental Gold Nanoparticles Based on the Gold-Containing Nanocomplexes Prepared by Electrochemical Methods in Aqueous Solutions

Abstract: We report here the first electrochemical pathway to prepare Au-containing nanocomplexes with the mean diameter of 2 nm in 0.1 N KCl aqueous solutions without addition of any stabilizer. Encouragingly, polypyrrole-(PPy-) coated gold nanocomposites with a core-shell structure and a diameter smaller than 8 nm can be prepared by the formation of self-assembled monolayers and further orderly autopolymerization of pyrrole monomers on these nanocomplexes. The prepared Au/PPy nanocomposites should exhibit extremely hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 34 publications
(49 reference statements)
8
76
0
1
Order By: Relevance
“…The UV spectra of PPy/Cu in CA showed two absorption peaks at 295 and 460 nm, assigned to the π-π* transition and to the formation of perninfreaniline form (PB) and the spectra of PPy/Cu synthesized in SA and SB indicated a shoulder respectively at 360 and 350 nm, which was assigned to the formation of polybenzoic salt. AuCl 4 -nano complex showed a band at ~308 nm which disappeared after addition of Py monomer and a new band of π-π* transition of PPy appeared in the region 400-500 nm with absorption maximum at 463 nm, showing the formation of Au/PPy nanocomposite with core-shell structure (Liu & Chuang, 2003). The UV-visible absorption spectrum of pure PPy indicated (Konwer et al, 2011) a weaker absorption at 330 nm (π-π* transition) and stronger absorption at 570 nm (bipolar state of PPy).…”
Section: Infra Red (Ir)/raman/uv-visible Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The UV spectra of PPy/Cu in CA showed two absorption peaks at 295 and 460 nm, assigned to the π-π* transition and to the formation of perninfreaniline form (PB) and the spectra of PPy/Cu synthesized in SA and SB indicated a shoulder respectively at 360 and 350 nm, which was assigned to the formation of polybenzoic salt. AuCl 4 -nano complex showed a band at ~308 nm which disappeared after addition of Py monomer and a new band of π-π* transition of PPy appeared in the region 400-500 nm with absorption maximum at 463 nm, showing the formation of Au/PPy nanocomposite with core-shell structure (Liu & Chuang, 2003). The UV-visible absorption spectrum of pure PPy indicated (Konwer et al, 2011) a weaker absorption at 330 nm (π-π* transition) and stronger absorption at 570 nm (bipolar state of PPy).…”
Section: Infra Red (Ir)/raman/uv-visible Absorption Spectroscopymentioning
confidence: 99%
“…In the GNS/PPy composite, as GNS percentage increased, the broad peak shifted from 2θ ≈ 26º to 24.8º, implying that interaction occurs between GNS and PPy. The Au/PPy core-shell nanocomposites (Liu and Chuang, 2003) (Vishnuvardhan et al, 2006). Zhang et al, (2011) recorded the FTIR of pure PPy and PPy/GNS composite and observed that most of peaks, which correspond to PPy, get shifted towards the left when GNS was introduced.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…[7,8] Electrochemical polymerization is a fast and easy method to prepare films made of conductive polymers and their composites with high conductivity but the problem of this method is that producing conductive polymers in the scales which are larger than laboratory scale is difficult. [9] Composites of poly(3,4-ethylenedioxythiophene) (PEDOT)/ITO, [10] polypyrrole(PPy)/Au, [11,12] polyaniline(PANI)/Au [5], and PPy/TiO 2 [13] were prepared via electrochemical method.…”
Section: Introductionmentioning
confidence: 99%
“…These novel PMEs may potentially find application in a wide range of technologies including, energy storage systems [3], membrane gas separation [4], electrocatalysis [5], and sensors [6]. The polymeric films can be further incorporated by some modifiers such as enzymes [7], nanoparticles [8] and polymer composite structures [9] to facilitate certain applications. Since the pioneering work of Diaz and coworkers in the late 70s [10,11], the fabrication of modified electrodes with highly stable and conductive polymeric films (polypyrrol, polyaniline, and polythiophene) has been a further developmental step towards their effective application in corrosion inhibition [12], light emitting diodes [13], electro-photosensitization [14] and biosensors [15].…”
Section: Introductionmentioning
confidence: 99%